Design Implementation Management Information System With A Case Study At The Madya Branch Lppnpi Perum Surabaya - Kusindra Arsa Huda; Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
Perum LPPNPI or AirNav Indonesia is a company, that focuses on air traffic services in Indonesia. More than 5000 employee’s overall and 179 employees on the Airnav branch of Surabaya, where was the employees management just manual processed for printing of decree documents, data processed and administered documents. So need an Rancang Bangun Penerapan Sistem Informasi Management Kepegawaian Dengan Studi Kasus Di Perum LPPNPI Cabang Madya Surabaya. With an information system could implement a modern process for printing of decree documents, data processed and administered documents on that company. The information system is web base with PHP language and Mysql Database, that used waterfall method, start from a survey, collected data, analysis, plan/Design system, implementation/coding and testing. The system had 16 structure table : Kategori Kantor, Kantor, Detail Kantor, Karyawan, Jenis Jabatan, Formasi, Jabatan Karyawan, Alamat, Kategori Identitas, Identitas, Komunikasi, Pendidikan, Keluarga, Pelatihan dan Pejabat. The Information System modernizes data processing, administration, and printing of decree documents in a business, improving the effectiveness and efficiency of the administrative process with digital process, so better for saving important data, paperless and be go green company on industry 4.0 technologies.